Local banks and the effects of oil price shocks - Wang, Teng (Journal of Banking & Finance, 2021)
This paper studies the effects of the oil price shocks on local banks, and the propagation of the shocks through banks’ branching networks. Exposed banks with significant operations in oil-concentrated counties experienced a decline in demand deposit, a surge in credit line drawdowns, and a jump in troubled loans. Facing liquidity pressure, banks were forced to sell liquid assets, offer higher deposit rates, and reduce lending to small businesses and mortgage borrowers in unaffected markets. The effect is magnified when banks do not have strong community ties, while it is mitigated if banks have higher liquidity buffers, or sufficiently dispersed branching networks. I further document that healthy unexposed banks’ capacity to substitute credit supply is quite limited, providing fresh evidence from the perspective of bank competition.